The Role of Place- Names in Olof Sirma’s two Yoik Texts and their Translations - Zorgdrager, Nellejet (Journal of Northern Studies, 2018)
This article discusses the place-names in two old Sami yoik songs. These songs, provided by Olof Sirma, a Sami student, were published in Sami and Latin in Schefferus’ book Lapponia in 1673. They became known as the winter song and the summer song. The winter song is a kind of travel account in which a lover tells about his journey by reindeer sledge. In the summer song he dreams about his absent love. Before the end of the twentieth century both love songs were translated many times into various languages. The article takes up the placenames, the landscape described in the songs as well as the homeland of Sirma and the places mentioned in the texts. It discusses what the respective translators did with the place-names from the Latin source texts, in what way they changed the landscape in their translated versions, how, through misreading, a place-name could become the name of a girl or how a place-name was used for personal ends as proof of a questionable thesis. When, in the twentieth century, translators turned to the Sami source texts, the original landscape gradually emerges again.